2016
DOI: 10.1002/prot.25189
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a glycoside hydrolase family 50 enzyme from a subfamily that is enriched in human gut microbiome bacteroidetes

Abstract: The polysaccharide utilization locus in Bacteroides plebeius that confers the ability to catabolize porphyran contains a putative GH50 β-agarase (BACPLE_01683, BpGH50). BpGH50 did not show any clear activity on agarose or on the related algal galactans porphyran and carrageenan. However, the 1.4 Å resolution X-ray crystal structure of BpGH50 confirmed its possession of the core (α/β) barrel fold found in GH50 enzymes as well as the structural conservation of the catalytic residues and some substrate binding re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Second, we attempted to determine the activity of Bp GH50, which possibly takes part in the next step of the agarose degradation pathway by degrading neoagarooligosaccharides (NAOSs; agarooligosaccharides with AHG on the non-reducing end) into NeoDP2. As previously reported 33 , Bp GH50 did not exhibit an exo-type β-agarase activity producing NeoDP2 toward agarose (Fig. 2 C).…”
Section: Resultssupporting
confidence: 87%
“…Second, we attempted to determine the activity of Bp GH50, which possibly takes part in the next step of the agarose degradation pathway by degrading neoagarooligosaccharides (NAOSs; agarooligosaccharides with AHG on the non-reducing end) into NeoDP2. As previously reported 33 , Bp GH50 did not exhibit an exo-type β-agarase activity producing NeoDP2 toward agarose (Fig. 2 C).…”
Section: Resultssupporting
confidence: 87%
“…Three crystal structures of GH50 agarases have also been determined—exo‐β‐agarase (Aga50D) from Saccharophagus degradans (PDB ID: 4BQ2), β‐agarase from Bacteroides plebeius (PDB ID: 5T3B), and an exo‐β‐agarase from A. gilvus WH0801 (PDB ID: 5Z6P). These enzymes display a core (α/β) 8 ‐barrel fold and the key Glu residues are well conserved (Figure 8D, 8E, and 8F) (Giles, Pluvinage, & Boraston, 2016; Pluvinage, Hehemann, & Boraston, 2013; Zhang et al., 2019). Enzyme kinetics and degradation pattern data obtained with various oligosaccharides of agarose with AgaB from Pseudoalteromonas sp.…”
Section: Marine‐polysaccharide Degrading Enzymesmentioning
confidence: 99%
“…Previous studies have shown that heat stress can alter the gut microbiota of mice [ 17 ]. The Firmicutes to Bacteroidetes ratio decreased significantly under 30 °C [ 18 ]. Short-chain fatty acids (SCFAs) are metabolites formed by gut microbes from complex dietary carbohydrates.…”
Section: Introductionmentioning
confidence: 99%